Determining the features of loading the bearing structure of a multifunctional car under operating modes - Fomin, Oleksij; Lovska, Alyona; Lytvynenko, Andrii; Sova, Sergiy (Eastern-European Journal of Enterprise Technologies, 2022)
This paper substantiates the modernization and commissioning of a railroad car for high-temperature, bulk/loose cargoes in order to improve the efficiency of railroad transportation. A feature of the car is the presence of an open-type boiler, which is made of heat-resistant material. To prevent splashing of transported cargo, it is possible to use a removable cover, which is attached to the top of the boiler. The boiler of the car was calculated for strength under the main operating modes. The vertical load on the boiler was taken into consideration while accounting for the transportation of bulk cargo, as well as longitudinal, and the effect of temperature load. The strength was calculated by the method of finite elements. It is taken into consideration that the boiler is made of composite heat-resistant material. The calculation results showed that with the considered load modes, the strength of the boiler is ensured. The dynamic load of the boiler was mathematically modeled at car shunting. The calculation was performed in a flat coordinate system. Solving the mathematical model of the car dynamic load has established that the maximum acceleration that acts on the boiler is 36.5 m/s2. The dynamic load of the boiler was simulated. The dislocation fields and numerical values of accelerations that act on it were determined. The maximum acceleration, in this case, is concentrated in the bottom of the boiler; it is 37.4 m/s2. To verify the dynamic load model, the F-criterion was used for calculation. It has been established that the hypothesis about the adequacy of the model is confirmed. The study reported here could contribute to improving the efficiency of railroad transport operation and advancing the design of multifunctional car structures.